Incidence of catastrophic health expenditure in Costa Rican households 2004 and 2013 - Briceño Chamorro, Rodrigo (2017)
Objetive: Identify the percentage of households whose out-of-pocket expenditures turn out to be a financial catastrophe (thirty to forty percent of household income). Methods: The World Bank's Research and Development Group Equity and Financial Protection module ADePT software is used along with a series of programmable routines that replicate the catastrophic expenditure analysis methodology of the study developed by Knaul, Wong, and Arreola-Ornelas (2012). Results: The incidence of catastrophic expenditure increased slightly from 0.6 percent of households in 2004 to 0.8 percent in 2013. Conclusions: The incidence of catastrophic health expenditure in Costa Rican households is not a problem for the Costa Rican health system, but the concern should be issue targeted.